Teaching Reading Strategies for Eight Grade of SMPN 1 Jereweh - Erlin Pebriantika; Erni Sona Aristia (Universitas Pendidikan Mandalika, 2021)
Reading English text as a basic language skill has a complicated process to be absorbed by second language learners. In practice, Text-based has enlarged students to the complicated of reading comprehension. Therefore, various kinds of teaching reading strategies appropriate to students’ characters and needs are determined. This study aimed to identify teaching reading strategies that English teachers frequently use and identify students’ reading achievement by applying certain recommended strategies and identifying its effect in the teaching and learning process. The subject was thirty students in the eighth grade of SMPN 1 Jereweh, Academic Year 2019/2020. Data collection procedures were FGD, In-depth Interview, Observation, and a reading test. The reading test was distributed toward the Pre-test and Post-test. While the data analysis was a qualitative and inferential statistic. The findings showed two kinds of teaching reading strategies that were frequently applied by English teachers in SMPN 1 Jereweh, namely, SQ3R and QAR. By designing a new combination between both of those strategies, students reading comprehension achievement showed that dominantly students’ categorized in “Good “level. The mean score was significantly different (Pre-test= 55.83, while Post-Test= 78.92). In addition, the r = 0.00 < 0.05 meant that there were significant effects before and after implementing SQ3R and QAR strategies. Thus, this design was recommended for teaching reading comprehension.